2021
DOI: 10.31557/apjcp.2021.22.6.1799
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nuclear Encoded Mitochondrial Gene Networks in Cervical Cancer

Abstract: Cervical cancer (CC) is a significant public health problem affecting women in countries with low resource settings. According to the Global Cancer Observatory database, there were 570,000 cases and 311,000 deaths due to CC in 2018 (Ferlay et al., 2018). Over a third of the overall global CC cases were contributed together by India and China. In 2018, the CC cases in India and China were 97,000 and 106,000, respectively, with mortality of 60,000 and 48,000, respectively (Arbyn et al., 2020;Bray et al., 2018). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…9 a). The suggested drugs of our study also reported by the other researchers such as Docetaxel [ 70 , 91 ], Temsirolimus [ 72 , 74 , 88 , 89 ], Paclitaxel [ 14 , 70 , 73 , 80 , 82 , 87 , 89 , 91 ], Vincristine [ 14 , 70 , 91 ], Everolimus [ 89 ], Vinorelbine [ 14 , 73 , 91 ], cabazitaxel [ 90 ], Lapatinib [ 74 , 86 , 88 , 89 ], Irinotecan [ 73 , 91 ], Imatinib[ 88 90 ] for the treatment of CC infections (see Fig. 9 b).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…9 a). The suggested drugs of our study also reported by the other researchers such as Docetaxel [ 70 , 91 ], Temsirolimus [ 72 , 74 , 88 , 89 ], Paclitaxel [ 14 , 70 , 73 , 80 , 82 , 87 , 89 , 91 ], Vincristine [ 14 , 70 , 91 ], Everolimus [ 89 ], Vinorelbine [ 14 , 73 , 91 ], cabazitaxel [ 90 ], Lapatinib [ 74 , 86 , 88 , 89 ], Irinotecan [ 73 , 91 ], Imatinib[ 88 90 ] for the treatment of CC infections (see Fig. 9 b).…”
Section: Discussionsupporting
confidence: 87%
“…Several research groups already suggested transcriptome-guided different sets of repurposable drugs for the treatment against CC [ 23 , 24 , 69 , 70 , 72 91 ]. We collected host transcriptome-guided 80 meta-drug agents by the literature review of CC disease [see Table S2] for exploring candidate drugs.…”
Section: Methodsmentioning
confidence: 99%
“…Then, we selected top-ranked three drugs as the candidate drugs, where the first three drugs showed strong binding affinities with all target proteins ( Figure 6 ), where red * denoted published and proposed receptors, and blue ** denoted published receptors. Some other independent studies also recommended our suggested drugs, including Vincristine [ 56 , 57 ], Vinorelbine [ 57 , 58 ], and Paclitaxel [ 56 , 57 , 58 , 59 , 60 ], for the treatment against CC. Finally, we examined the stability of top-ranked three drugs (Vincristine, Vinorelbine, Paclitaxel) by using 100 ns MD-based MM-PBSA simulations for three top-ranked proposed receptors (AURKA, CDK1, TOP2A) and observed their stable performance according to the laws of physics [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…TACCO provides information about DEGs in 26 different cancer types from the TCGA datasets. TACCO can be used for pathway analysis and prognostic model construction using input gene lists 25 , 110 . We identified the DEHGs between tumor and normal tissue samples in the TCGA-HNSCC data set, using the "select DEGs" option with a parameter cutoff p -value ≤ 0.05 and expression of log2 fold change > + 2 and < − 2, calculated using EBSeq, Wilcoxon rank-sum test and multiple test correction 25 .…”
Section: Methodsmentioning
confidence: 99%